The development of the attitude scale study in operating systems and application lessons - Kazu, Ibrahim Yaşar; Özdemir, Oğuzhan; Erten, Pinar (T.C. Milli Egitim Bakanligi, 2016)
Hereby is intended an attitude scale development for operating systems and application lessons, which it will determinating students attitudes. After literature screening is cerated a pool, in which is included 50 items in different sizes of attitudes. The content validity of these items are supplied their aim suitability and the adequancy of represents the subject in accordance with experts views. This study is actualized with 129 students, that they are educated in 3 different Universities CITE of department and taken operating systems and application lessons in advance. In analyse results hav been found the Cronbach Alpha internal consistency coefficient.969 and described total variance as %57.967. The load factor values of substances are changed between.847 and.460. The two scale with 38 items, that it is divided in 2 factors as "positive attitude" and "negative attitude", is proved their validity and reliability.
Işletim sistemleri ve uygulamalari dersine yönelik tutum ölçeğinin geliştirilmesi çalişmasi
Keywords: Attitude scale; Reliability; The operating systems and applications; Validity